First Harvestman Record for the Juan Fernández Archipelago, Chile, with Morphological Notes on Acropsopilio chilensis (Opiliones: Caddidae: Acroposopilioninae) - Pérez-González, Abel; Ramírez, Martín J.; Soto, Eduardo M.; Pizarro-Araya, Jaime (Zootaxa, 2014)
Acropsopilio chilensis Silvestri, 1904 (Eupnoi: Caddidae: Acropsopilioninae), is recorded for Robinson Crusoe Island, Chile. This is the first harvestman species recorded for the Juan Fernández Archipelago and also the first extra-continental record for this species. During the comparison with continental co-specific specimens, some previously unknown, remarkable morphological characteristics were discovered, among them: the absence of ovipositor seminal receptacles and tracheal system, small and probably imperforate spiracles and the presence of a subdistal spiny structure, maybe a stylus, in the major branch of the penis.